2022
DOI: 10.1109/access.2022.3178437
|View full text |Cite
|
Sign up to set email alerts
|

A Novel LoRa LPWAN-Based Communication Architecture for Search & Rescue Missions

Abstract: To avoid risking the lives of rescue team personnel in the event of disasters like earthquakes, volcanic eruptions, hurricanes, etc., Search and Rescue (SAR) robots are increasingly incorporated into the operation. One of the major challenges in integrating SAR robots into rescue operations is the potentially severely damaged infrastructure within the disaster site. A functional communication system is critical for exchanging real-time information between the robots and the base station. Given the limited cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Manuel et al [ 24 ] suggested a novel communication architecture for a search and rescue (SAR) mission. This architecture is based on the LoRaWAN, and a SAR robot called “Rescuer”, which can be deployed in areas where all communication networks are supposed to be wiped out.…”
Section: Related Workmentioning
confidence: 99%
“…Manuel et al [ 24 ] suggested a novel communication architecture for a search and rescue (SAR) mission. This architecture is based on the LoRaWAN, and a SAR robot called “Rescuer”, which can be deployed in areas where all communication networks are supposed to be wiped out.…”
Section: Related Workmentioning
confidence: 99%
“…The node challenge ensemble is subscribed to the /camera/image topic so that it can receive the data published by the camera [14] [15]. The data is a message-type Image from the sensor msgs.msg package.…”
Section: A Short Overviewmentioning
confidence: 99%
“…By cutting the lidar [9] signal, it can detect and avoid obstacles. At the same time, we refer to the OpenCV library to realize the visual analysis of the images captured by the camera [10], realize the map drawing through SLAM [11] [12], and realize functions such as autonomous navigation in different areas (challenges). In our experiments, we simulated three different environments as challenges and tested the specific performance of different sensors, as well as autonomous obstacle avoidance and mapping capabilities, using two sensors in each environment alone or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are increasingly employed in a wide array of applications. Their capabilities are demonstrated in search and rescue missions, where multiple robots can cover larger areas faster than a single robot [2][3][4][5]. In surveillance tasks [6], multi-robot systems can monitor larger perimeters, ensuring enhanced security.…”
Section: Introductionmentioning
confidence: 99%